Criterios del daño moral en el ordenamiento jurídico ecuatoriano - Pesantez Suriaga, Irma Estefania; Revilla Jaramillo, Johnny Marcelo (Machala, 2022)
This research article consists of exploring and unifying the theoretical bases of non-pecuniary damage under the perspectives of different doctrinaires at the national and international level, for this, as the main objective, the analysis of the configuration of non-pecuniary damage and possible reparations measures will be addressed. with main focus on the Ecuadorian legislation. Using a qualitative and documentary study for the elaboration of a theoretical base referring to moral damage; the use of exegetical, descriptive, analytic-synthetic, comparative and hermeneutical methods. Concluding, that although it is true that in Ecuadorian legislation as such it is not defined that it is moral damage, from Title XXXIII “Of Crimes and Quasi-crimes” of the Civil Code, it can be seen in article 2232, third paragraph, that “ Reparation for non-pecuniary damages may be sued if such damages are the result of the defendant's unlawful action or omission, leaving the judgment of the judge to determine the value of the compensation (…) ”, however, it is important to note that the judge must have a clear idea what the plaintiff of the action intends, and for this the victim must detail his claims in the lawsuit in the respective part of "amount", and in this way, the interests of the affected part.
El presente artículo de investigación consiste en explorar y unificar las bases teóricas del daño moral bajo las perspectivas de diferentes doctrinarios a nivel nacional e internacional, para ello, como objetivo principal se abordará el análisis de la configuración del daño moral y las medidas de reparaciones posibles con principal enfoque en la legislación ecuatoriana. Empleando un estudio cualitativo y documental para la elaboración de una base teórica referente al daño moral; el uso de los métodos exegéticos, descriptivo, analítico- sintético, comparativo y hermenéutico. Concluyendo, que si bien es cierto que en la legislación ecuatoriana como tal no se define que es el daño moral, a partir del Título XXXIII “De Los Delitos y Cuasidelitos” del Código Civil, se puede apreciar en el articulado 2232 inciso tercero, que “la reparación por daños morales puede ser demandada si tales daños son el resultado próximo de la acción u omisión ilícita del demandado, quedando a la prudencia del juez la determinación del valor de la indemnización (…)”, sin embargo, es importante rescatar que el juez debe tener una idea clara que es lo que pretende la parte actora de la acción, y para ello la víctima deberá detallar sus pretensiones en la demanda en la parte respectiva de “cuantía”, y de esta manera, se podrá resguardar los interéses de la parte afectada.
Keywords: DAÑO MORAL; DERECHO; PROTECCION; DOCTRINA